A Javanese Dance is A Representation of Rasa in Javanese Culture - Indah Sulastuti, Katarina; Sunardi; Efrida; Mamik Widyastuti; Hadawiyah Endah Utami; Setya Widyawati; Budi Setyastuti; Nuryanto (Mudra Jurnal Seni Budaya, 2024)
This paper presents the concept of rasa in Javanese culture embodied in Javanese dance. The ethnographic approach in the Ethnochoreology discipline used as a step in data collection was in-depth interviews with actors (dancers, choreographers) in a society with a Javanese cultural scope. The observation step in the data collection effort was carried out using the involved observation model or participant observer, completed by data collection through literature and relevant documents. The theoretical perspective and concept used as the basis for thinking in discussing the case study of the Ela-ela dance in this paper is the concept of rasa, as put forward by Paul Stange. Namely, that rasa is a "tool" or "means" of perception, or a "function" of "whisper of heart or intuition", and rasa in Javanese dance as expressed by Katarina Indah Sulastuti, that rasa in Javanese dance is an element that is integrated with the senses in the body in a comprehensive manner which involves: the sensibility of heart vibrations, sharpness of intuition, imagination, bodily intelligence, and understanding of Javanese culture. Javanese dance, in the example of the case study, the Bedhaya Ela-ela dance is a representation of the rasa in Javanese culture, namely that the Bedhaya Ela-ela dance is a form of dance that substantially depicts the life of the Javanese people and the culture of rasa which involves issues of ethics, aesthetics, and religion in Javanese culture.